2008
DOI: 10.1523/jneurosci.3015-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Swiss Cheese, a Protein Involved in Progressive Neurodegeneration, Acts as a Noncanonical Regulatory Subunit for PKA-C3

Abstract: The Drosophila Swiss Cheese (SWS) protein and its vertebrate ortholog Neuropathy Target Esterase (NTE) are required for neuronal survival and glial integrity. In humans, NTE is the target of organophosphorous compounds which cause a paralyzing axonal degeneration and recently mutations in NTE have been shown to cause a Hereditary Spastic Paraplegia called NTE-related Motor-Neuron Disorder. SWS and NTE are concentrated in the endoplasmic reticulum and both have been shown to have an esterase function against an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 39 publications
3
55
0
1
Order By: Relevance
“…For example, recent work has shown that the Drosophila NTE homologue SWS binds to cAMP protein kinase (PKA) catalytic subunit C3 and acts similarly to the PKA R1 regulatory subunit to inhibit PKA-C3 (Bettencourt da Cruz et al, 2008). Furthermore, neurodegeneration in sws Drosophila mutants is exacerbated by increased PKA-C3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent work has shown that the Drosophila NTE homologue SWS binds to cAMP protein kinase (PKA) catalytic subunit C3 and acts similarly to the PKA R1 regulatory subunit to inhibit PKA-C3 (Bettencourt da Cruz et al, 2008). Furthermore, neurodegeneration in sws Drosophila mutants is exacerbated by increased PKA-C3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…To substantiate these results, interaction analyses with homologous R subunits have to be performed. Recently, the D. melanogaster protein Swiss cheese was identified as a non-canonical R subunit binding to DC2, inhibiting both DC2 and the esterase activity of Swiss cheese mainly in the brain (44). Whether this regulation is conserved in mammalian tissues, awaits experimental evaluation, but this also points to the functional separation of conventional PKA and PrKX-like kinases.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, NTE is required for axonal maintenance. In addition, SWS acts as a noncanonical regulatory subunit to regulate the localization and kinase activity of the C3 catalytic subunit of PKA (PKA-C3), and disruption of this regulation can induce neurodegeneration (Bettencourt da Cruz et al, 2008).…”
Section: Biological Functionmentioning
confidence: 99%